Formulasi Sediaan Spray Alami dari Limbah Kombucha Bunga Telang sebagai Produk Bioteknologi Pertanian dan Farmasi dalam Menghambat Pertumbuhan Jamur Patogen pada Jambu Air (Syzygium aqueum) - Rezaldi, Firman; Ngete, Ani Florida (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Water guava is one of the easiest horticultural commodity plants to cultivate in the home garden. Water guava has an important role as a functional food and pharmaceuticals (medicines and cosmetics). A common problem that occurs in water guava cultivation activities is an increase in fungal infections that appear one-sidedly like dew. The pathogenic fungus referred to in increasing infection of the water guava is the species Capnodium sp. An environmentally friendly solution to inhibiting the growth of pathogenic fungi for water guava is to utilize the fermented waste of butterfly pea flower kombucha at sugar concentrations of 20%, 30% and 40% as has been done in previous research. This research aims to inhibit the growth of the Capnodium sp fungus from the fermentation waste of butterfly pea flower kombucha in sugar concentrations of 20%, 30% and 40%. The research is laboratory experimental, namely by preparing butterfly pea flower kombucha fermentation waste in sugar concentrations of 20%, 30% and 40%, preparing positive and negative control solutions. The antifungal testing method is carried out via disc diffusion. Data analysis was carried out via one-way ANOVA and post hoc tests. The results of this research have shown that based on a one-way ANOVA test with a P value < 0.05 followed by post hoc analysis, the sugar concentration in butterfly pea flower kombucha fermentation waste is 40% different from 20% and 30% as an antifungal Capnodium sp. The conclusion of this research is that butterfly pea flower kombucha fermentation waste can be used as a natural spray preparation to inhibit the growth of the Capnodium sp fungus and can also be used as an agricultural and pharmaceutical biotechnology product which is quite environmentally friendly in minimizing the use of chemical pesticides